Daily links between Latinx siblings' relationship qualities and mood. Issue 5 (3rd May 2022) - Hochgraf, Anna K.; Son, Daye; Updegraff, Kimberly A.; McHale, Susan M.; Umaña‐Taylor, Adriana J.
Abstract: This study examined daily links between sibling warmth and negativity and positive and negative mood in middle childhood and the moderating role of enculturation. Participants were 326 Latinx children from 163 families in the United States ( M age  = 10.63 and 8.58 years for older and younger siblings, 48.5% female, 89.3% Mexican‐origin). Children reported their days' experiences during seven nightly phone interviews conducted in 2018–2019. Multilevel analyses revealed within‐person, positive associations between daily sibling warmth and positive mood ( OR = 1.81, 95 % CI = [ 1.25, 2.62 ] ), and sibling negativity and negative mood ( OR = 3.21, 95 % CI = [ 2.12, 4.86 ] ) . Moreover, for more enculturated children, odds of positive mood were lower on days when they experienced more sibling negativity than usual. Findings document the significance of Latinx children's daily sibling experiences.